Psychometric properties of the Incivility in Nursing Education - Revised Survey - Brazilian version - Vanessa dos Santos Ribeiro; Cynthia M. Clark; Claudia Benedita dos Santos; João Marôco; Jonas Bodini Alonso; Aline Helena Appoloni Eduardo; Emilia Campos de Carvalho (Universidade de São Paulo, 2024)
Abstract Objective: to analyze the psychometric properties of the Incivility in Nursing Education - Revised Survey - Brazilian version with undergraduate nursing students. Method: methodological study conducted in a nursing school in São Paulo state. It is the analysis of the psychometric properties (reliability and construct validity) of the items in the INE-R survey - Brazilian version. Construct validity was performed by Confirmatory Factor Analysis, and reliability by test-retest in order to verify the instrument's stability, as calculated by the Intraclass Correlation Coefficient and the Internal Consistency of the items according to Cronbach's alpha, ordinal alpha and McDonalds's omega coefficients. Results: Confirmatory Factor Analysis fitted the proposed model with two factors (low and high incivility), with a suggestion to exclude one of student items. Most of the fitting values for the student items and all of the faculty-member items complied with the references established in the literature; the values for Internal Consistency Coefficients were greater than 0.80, and Intraclasss Correlation Coefficients were greater than 0.75. Conclusion: the Brazilian version of the Incivility in Nursing Education - Revised Survey is validated for the studied context, as it has shown satisfactory reliability and validity by means of factor analysis, which has confirmed the original two-factor model, with 23 items addressing student behaviors and 24 items applied to faculty behaviors.